BIM-based assessment metrics for the functional flexibility of building designs - Cavalliere, Carmine; Dell'Osso, Guido Raffaele; Favia, Fausto; Lovicario, Marco (Automation in construction, 2019)
The standards development, technological advancement, and lifestyle evolution lead to different scenario in the construction sector, such as the users adapting to the buildings, the buildings adapting to the users, the demolition of the buildings or parts of them, which increase the waste production and resources depletion. On this background, there is a need to conceptualize the buildings flexibility aspects into sustainability-led design. This paper proposes a novel approach to evaluate the flexibility level of buildings by introducing six selective criteria, which are implemented in a BIM environment by coupling Building Information Modelling (BIM) and Visual Programming Language (VPL) tools. The results show that it is possible to automatically calculate the flexibility of buildings during the design process phases. Therefore, the real-time iteration potential of the method provides information for the decision-making process as a means of guiding designers towards more flexible and sustainable design choices. •Metrics to calculate the flexibility level of buildings.•Multi-criteria decision approach to identify the weight of flexibility criteria.•Use of BIM-based approach to implement the flexibility metrics.•Use of Visual Programming Language tool to automatically perform the calculation.•Flexibility metrics as a decision-making tool to reach more sustainable solutions.